On the taxonomic status of amphidromous shrimp Paratya borealis Volk, 1938 (Crustacea: Decapoda: Atyidae) from the south of the Russian Far East - Marin, Ivan (Zootaxa, 2018)
One of the most northern representatives of the family Atyidae, an amphidromous shrimp Paratya borealis Volk, 1938 (Crustacea: Decapoda: Atyidae), is considered as a junior synonym of Paratya compressa (De Haan, 1844 [in De Haan, 1833-1850]) based on morphological and genetic investigations of the specimens collected in rivers flowing into Peter the Great Bay and Posyeta Bay along the Russian coasts of the Sea of Japan. The study greatly increases the area of distribution of P. compressa to north for more than 1000 km and suggests that the species probably inhabit rivers flowing into the Sea of Japan also along North and South Korean coasts.